2019
DOI: 10.3390/cells8070739
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Neuroinflammatory Effect of Alantolactone through the Suppression of the NF-κB and MAPK Signaling Pathways

Abstract: Neuroinflammation is a major cause of central nervous system (CNS) damage and can result in long-term disability and mortality. Therefore, the development of effective anti-neuroinflammatory agents for neuroprotection is vital. To our surprise, the naturally occurring molecule alantolactone (Ala) was reported to significantly inhibit tumor growth and metastasis as a result of its excellent anti-inflammatory effects. Thus, we proposed that it could also act as an anti-neuroinflammatory agent. Thus, in this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 50 publications
1
30
0
Order By: Relevance
“…An obvious further direction of research into the activity of new compounds is the study involving immune cells, e.g., through the use of co-cultures of microglia and neuronal cells. The involvement of immune cells would additionally investigate the indirect effects of LPS on neuronal cells, primarily through the proinflammatory cytokines IL-1β and IL-6 [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An obvious further direction of research into the activity of new compounds is the study involving immune cells, e.g., through the use of co-cultures of microglia and neuronal cells. The involvement of immune cells would additionally investigate the indirect effects of LPS on neuronal cells, primarily through the proinflammatory cytokines IL-1β and IL-6 [9].…”
Section: Discussionmentioning
confidence: 99%
“…From several studies, it is known that the proinflammatory effect of LPS on PC12 cells is based on activation of the TLR4 (Toll-like receptor 4). Activation of the TLR4 receptor induces NF-κB transcription factor, which promotes the expression of proinflammatory cytokines and chemokines [9,14,17,40]. The treatment of PC12 cells with LPS at a concentration of 1 mg/mL for 18 h resulted in an approximately six-fold increase in NF-κB compared to the control [20].…”
Section: Discussionmentioning
confidence: 99%
“…For such CNS injury, the neurotrophic factor plays an important role in promoting the functional recovery and maintenance. 39 , 40 It has been reported that HSYA could increase the content of the BDNF protein and exert neuroprotective effects on cerebral ischemic injury. 41 As shown in Figure 10 , CIR resulted in the down-regulation of BDNF expression.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, formononetin mediated neuroprotection against cerebral ischemia/reperfusion in rats via downregulation of the Bax/Bcl-2 ratio and upregulation PI3K/Akt signaling pathway [67]. MAPK signaling pathways may be a therapeutic targets for stroke [68]. Researches showed that suppressing the NF-κB and MAPK signaling pathways would down regulate the expression of proin ammatory factors.…”
Section: Discussionmentioning
confidence: 99%
“…Researches showed that suppressing the NF-κB and MAPK signaling pathways would down regulate the expression of proin ammatory factors. MAPK pathways could be a promising candidate for future applications in CNS injury treatment [69]. BHD alleviated pressure overload induced cardiac remodeling by suppressing TGF-β/Smads and MAPKs signaling activated brosis [70].…”
Section: Discussionmentioning
confidence: 99%